One week, but not 12 hours, of cast immobilization alters promotor DNA methylation patterns in the nNOS gene in mouse skeletal muscle. (9th October 2019) - Tomiga, Yuki; Ito, Ai; Sudo, Mizuki; Ando, Soichi; Eshima, Hiroaki; Sakai, Kazuya; Nakashima, Shihoko; Uehara, Yoshinari; Tanaka, Hiroaki; Soejima, Hidenobu; Higaki, Yasuki
Abstract : Key points: DNA methylation may play an important role in regulating gene expression in skeletal muscle to adapt to physical activity and inactivity. Neuronal nitric oxide synthase (nNOS) in skeletal muscle is a key regulator of skeletal muscle mass; however, it is unclear whether nNOS expression is regulated by DNA methylation. We found that 1 week of cast immobilization increased nNOS DNA methylation levels and downregulated nNOS gene expression in atrophic slow‐twitch soleus muscle from the mouse leg. These changes were not detected in non‐atrophic fast‐twitch extensor digitorum longus muscle. Twelve hours of cast immobilization decreased nNOS gene expression, whereas nNOS DNA methylation levels were unchanged, suggesting that downregulation of nNOS gene expression by short‐term muscle inactivity is independent of the DNA methylation pattern. These findings contribute to a better understanding of the maintenance of skeletal muscle mass and prevention of muscle atrophy by epigenetic mechanisms via the nNOS/NO pathway. Abstract: DNA methylation is a mechanism that controls gene expression in skeletal muscle under various environmental stimuli, such as physical activity and inactivity. Neuronal nitric oxide synthase (nNOS) regulates muscle atrophy in skeletal muscle. However, the mechanisms regulating nNOS expression in atrophic muscle remain unclear. We hypothesized that nNOS expression in atrophic muscle is regulated by DNA methylation of the nNOS promotor in soleus (Sol; slow‐twitch fibre dominant) and extensor digitorum longus (EDL; fast‐twitch fibre dominant) muscles. One week of cast immobilization induced significant muscle atrophy in Sol but not in EDL. We showed that 1 week of cast immobilization increased nNOS DNA methylation levels in Sol, although only a minor change was detected in EDL. Consistent with the increased DNA methylation levels in atrophic Sol, the gene expression levels of total nNOS and nNOSµ (i.e. the major splicing variant of nNOS in skeletal muscle) decreased. The abundance of the nNOS protein and cell membrane (especially type IIa fibre) immunoreactivity also decreased in atrophic Sol. These changes were not observed in EDL after 1 week of cast immobilization. Furthermore, despite the lack of significant atrophy, 12 h of cast immobilization decreased gene expression levels of total nNOS and nNOSµ in Sol. However, no association was detected between nNOS DNA methylation and gene expression. The expression of the nNOSβ gene, another splicing variant of nNOS, in EDL was unchanged by cast immobilization, whereas its expression was not detected in Sol. We concluded that chronic adaptation of nNOS gene expression in cast immobilized muscle may involve nNOS DNA methylation. Key points: DNA methylation may play an important role in regulating gene expression in skeletal muscle to adapt to physical activity and inactivity. Neuronal nitric oxide synthase (nNOS) in skeletal muscle is a key regulator of skeletal muscle mass; however, it is unclear whether nNOS expression is regulated by DNA methylation. We found that 1 week of cast immobilization increased nNOS DNA methylation levels and downregulated nNOS gene expression in atrophic slow‐twitch soleus muscle from the mouse leg. These changes were not detected in non‐atrophic fast‐twitch extensor digitorum longus muscle. Twelve hours of cast immobilization decreased nNOS gene expression, whereas nNOS DNA methylation levels were unchanged, suggesting that downregulation of nNOS gene expression by short‐term muscle inactivity is independent of the DNA methylation pattern. These findings contribute to a better understanding of the maintenance of skeletal muscle mass and prevention of muscle atrophy by epigenetic mechanisms via the nNOS/NO pathway.